La ville revisitée par les sportifs... ? - Christian Dorvillé; Claude Sobry (Territoire en Mouvement)
The appearance of new sports practices during the 70’s caused induced effects like a sportivisation of the society and a diversification of the practices places, in particular with urban spaces that the sport adopted (streets, car parks, etc.). These street sports turn the performance into a show and are participating in the animation of public places. Practices and clothes have become elements of the body identity for suburb teenagers. However the practice is less frequent that the use of sport signs. Wearing well known brand makes it possible to hide some social differences. All this leads to make the sport accessories market work.Sport is also a pretext to make trips converging to where the events take place. That’s what is called urban sporting tourism, recently made up term that requires further definition. This form of active participation and performances on competition spots as well as sport history.The organizing cities of major events, attracting major tourist flows, are expecting consequent economic benefit as well as job creation, even though some negative sides shouldn’t be ignored.